Cover Picture: Solvent‐Induced Self‐Assembly of Highly Hydrophobic Tetra‐ and Pentaphenylalanine Peptides (Isr. J. Chem. 6‐7/2015). Issue 6 (June 2015) - Arnon, Zohar; Adler‐Abramovich, Lihi; Levin, Aviad; Gazit, Ehud
<x xml:space="preserve">Abstract</x> The cover picture presents the ultrastructural morphology of tetra‐phenylalanine assembly prepared by a solvent‐switching technique. Imaging was performed using high‐resolution scanning electron microscopy. Read more in the Full Paper by Gazit and co‐workers on page 756.